2019
DOI: 10.1074/jbc.ra118.007236
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae inhibits purinergic signaling and promotes purinergic receptor P2Y2 internalization in alveolar epithelial cells

Abstract: Edited by Roger J. Colbran Bacterial pneumonia is a global health challenge that causes up to 2 million deaths each year. Purinergic signaling plays a pivotal role in healthy alveolar epithelium. Here, we used fluorophore-based analysis and live-cell calcium imaging to address the question of whether the bacterial pathogen Streptococcus pneumoniae directly interferes with purinergic signaling in alveolar epithelial cells. Disturbed purinergic signaling might result in pathophysiologic changes like edema format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…In vitro , investigations have revealed that S. pneumoniae can cause damage to alveolar epithelial cells ( 90 ). Similar results have confirmed that S. pneumoniae directly inhibits purinergic signaling by inducing purinergic receptor P2Y2 phosphorylation and internalization, which can lead to suppression of the calcium response of alveolar epithelial cells to ATP and affect the cellular integrity and function ( 91 ). Streptococcus may promote the development of lung cancer, although further experiments are needed for verification.…”
Section: Lung Cancer Biomarkerssupporting
confidence: 64%
“…In vitro , investigations have revealed that S. pneumoniae can cause damage to alveolar epithelial cells ( 90 ). Similar results have confirmed that S. pneumoniae directly inhibits purinergic signaling by inducing purinergic receptor P2Y2 phosphorylation and internalization, which can lead to suppression of the calcium response of alveolar epithelial cells to ATP and affect the cellular integrity and function ( 91 ). Streptococcus may promote the development of lung cancer, although further experiments are needed for verification.…”
Section: Lung Cancer Biomarkerssupporting
confidence: 64%
“…P2X 7 receptor has also been described to be required for the clearance of Streptococcus pneumoniae [ 52 ]. In a recent study, Oluto et al reported that Streptococcus pneumoniae inhibits purinergic signaling by increased internalization of P2Y 2 receptors in alveolar epithelial cells [ 202 ]. This might result in reduced surfactant secretion and subsequent alveolar collapse [ 95 ].…”
Section: The Role Of P2 Receptors In Lung Diseasementioning
confidence: 99%
“…Purinergic receptors are fundamental in understanding the COVID-19, because, in addition to being associated with the immune system, they have also been studied in the context of SARS, fibrosis, and blood clotting [ 25 ]. One of the receptors recently discussed in COVID-19 is P2X7, which is ionotropic, has an affinity for ATP, it is present in T cells, macrophages, neutrophils and DCs, and its function is to activate the cell types previously described and generate an inflammatory environment [ 11 , 20 , 26 ]. When activated by ATP, P2X7R rapidly promotes K + efflux, increased cytosolic Ca 2+ concentration, and release of cytokines, such as interleukin 1 beta (IL-1β) in neutrophils, in addition to activating the NLRP3 inflammasome [ 27 ].…”
Section: P2x7r As a Potential Therapeutic Targetmentioning
confidence: 99%
“…When activated by ATP, P2X7R rapidly promotes K + efflux, increased cytosolic Ca 2+ concentration, and release of cytokines, such as interleukin 1 beta (IL-1β) in neutrophils, in addition to activating the NLRP3 inflammasome [ 27 ]. IL-1β was found at high levels in patients affected by COVID-19 [ 20 , 26 , 28 ]. In general, the outcome of P2X7R signaling is the activation of effector T cells, T regulatory cells, natural killer T cells (NKT), monocytes, macrophages, and DCs.…”
Section: P2x7r As a Potential Therapeutic Targetmentioning
confidence: 99%
See 1 more Smart Citation